Serrated Adenoma Prevalence in Inflammatory Bowel Disease Surveillance Colonoscopy, And Characteristics Revealed by Chromoendoscopy and Virtual Chromoendoscopy - Marietta Iacucci; Cesare Hassan; Miriam Fort Gasia; Stefan Urbanski; Xianyong Gui; Bertus Eksteen; Gregory Eustace; Gilaad G Kaplan; Remo Panaccione (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Sessile or nonpolypoid neoplastic lesions, including sessile serrated adenomas (SSAs), are difficult to detect in patients with inflammatory bowel disease (IBD).